2018
DOI: 10.1017/s1041610218000686
|View full text |Cite
|
Sign up to set email alerts
|

The Going to Stay at Home program: combining dementia caregiver training and residential respite care

Abstract: Background: Caring for persons with dementia is stressful for family caregivers. Caregiver training programs and respite care can reduce this stress and help maintain persons with dementia living longer in the community. We evaluated a program that combines caregiver training with a residential respite stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 27 publications
(40 reference statements)
2
35
0
Order By: Relevance
“…Family carer-focussed interventions Have reduced carer burden and increased time lived at home by care recipients [36][37][38], probably because carers who are less stressed and burdened are more able to continue in supporting roles. UK Admiral Nursing Services work specifically with dementia family carers in some localities, but service content depends on local requirements and commissioning [39].…”
Section: Strategies For Delivering Carementioning
confidence: 99%
“…Family carer-focussed interventions Have reduced carer burden and increased time lived at home by care recipients [36][37][38], probably because carers who are less stressed and burdened are more able to continue in supporting roles. UK Admiral Nursing Services work specifically with dementia family carers in some localities, but service content depends on local requirements and commissioning [39].…”
Section: Strategies For Delivering Carementioning
confidence: 99%
“…12 The qualitative outcomes further supported the positive effects on self-reported needs in the "Going to stay at Home" program on which this intervention was based. 21 Moreover, the findings emphasize the importance of using a mixedmethods approach when considering psychosocial interventions if we are to avoid the limitations of randomized controlled trials that rely solely on quantitative data.…”
Section: Discussionmentioning
confidence: 94%
“…This program included psychological and educational themes and was delivered in informally structured group sessions with educational elements, group work, modeling, and role-play. 20,21 The results of a randomized controlled trial comparing waiting and control groups (respite care) showed that the training program effectively delayed nursing home admission, reduced mortality, reduced psychological morbidity, and lowered care costs. 20,[22][23][24] An extension study using a pre-post design in another setting produced comparable results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Their study was based on the Australian residential multicomponent training program which helped to heuristically and clinically explain caregiver strain. 2 Although previous studies have reported caregiver anxiety and depression as primary outcomes, 3 Birkenhäger-Gillesse et al reported that the primary outcome of their study was care-related QoL. We are interested to know why the primary outcome was changed.…”
mentioning
confidence: 98%